Impact of a Climate Smart Technology: Case of the Farmer Managed Natural Regeneration on Trees Biodiversity in Sudano-Sahelian Parklands of Kayes and Koulikoro, in Mali - Moussa, Zerome; Mahamadou, Diaby; Binta, Dansoko; Sayon, Keïta; Soumaïla, Maiga Boubacar; Kalifa, Traore; Mahamoudou, Famanta; Moise, Togo (Journal of Agricultural Studies, 2022)
In the Sahel, parklands are degraded due to climate change, human and animal pressure. The objective of this research was to assess the effect of Farmer Managed Natural Regeneration (FMNR) on trees biodiversity in Sudano-sahelian parklands of Kayes and Koulikoro, in Mali. Trees inventory was carried out in agricultural areas. The size of an inventory plot was 2500m². The inventory plots were 500 meters apart. The total area inventoried was 20 hectares. The woody flora of studied areas was made of 27 species of trees. Most represented families were Combretaceae (6 species); Mimosaceae (4 species) and Cesalpiniaceae (3 species). Families, species and genera of trees have varied according to the rural communities. In fact 8, 15, 12 and 11 species have been identified respectively in Tieneguebougou; Farako; Guemou and Bienkolobougou. The characteristic species has varied depending on studied areas with 2, 7, 3 and 3 species in respective localities. The index of regularity showed an identical high level of trees organization in Tieneguebougou, Guemou and Bienkolobougou. But, the index was low in Farako. A comparison of indexes values showed although the floristic composition was low in Tieneguebougou; Guemou and Bienkolobougou, their woody stand organization was further constant. The FMNR has increased the biodiversity of trees and consequently the volume of wood in agrarian areas. This biodiversity of trees contributes to carbon sequestration and strengthens the resilience of populations by providing them with goods (firewood, honey, etc.) and eco-systemic services. FMNR is a climate-smart technology, whose scaling up in Mali is essential.